2002
DOI: 10.1103/physrevb.66.134413
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of layered cobalt oxides investigated by muon spin rotation and relaxation

Abstract: Muon spin rotation-relaxation (SR) spectroscopy has been used to investigate the magnetic properties of polycrystalline Ca 3Ϫx M x Co 4 O 9 (xр0.5,M ϭSr,Y, and Bi͒ and Na 0.7 CoO 2 samples in the temperature range between 2.5 and 300 K. It was found that Ca 3 Co 4 O 9 exhibits a magnetic transition at around T c ϭ100 K; at lower temperatures, two types of relaxation were observed using a weak transverse field SR technique with Hϭ104 Oe: one with a fast relaxation rate F ϳ10 s Ϫ1 and the other with a slow S ϳ0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
131
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(153 citation statements)
references
References 15 publications
19
131
2
Order By: Relevance
“…Hsieh et al have shown that the decrease of T/S with lowering temperature originates from the decrease of the carrier concentration n according to Eq. (2) [18], which is also supported from the results of the Hall coefficient measurements [38], and proposed that this phenomenon is ascribed to an opening of the pseudogap caused by the short-range order of SDW below 100 K [19]. We also note that such a reduction of T/S below a pseudogap temperature is observed in other layered cobalt oxide [39] and the Kondo semiconductor CeNiSn [40].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Hsieh et al have shown that the decrease of T/S with lowering temperature originates from the decrease of the carrier concentration n according to Eq. (2) [18], which is also supported from the results of the Hall coefficient measurements [38], and proposed that this phenomenon is ascribed to an opening of the pseudogap caused by the short-range order of SDW below 100 K [19]. We also note that such a reduction of T/S below a pseudogap temperature is observed in other layered cobalt oxide [39] and the Kondo semiconductor CeNiSn [40].…”
Section: Discussionsupporting
confidence: 73%
“…The anomalous charge transport of this compound is clearly seen in the non-monotonic temperature variations of the electrical resistivity and the Seebeck coefficient [7,[12][13][14][15], but an underlying origin for these behaviors remains unclear. For instance, below T ∼ 60 K, the resistivity increases with decreasing temperature like an insulator while the Seebeck coefficient shows a metallic behavior, which has been discussed in terms of the variable range hopping [16], quantum criticality [17], and pseudogap opening [18] associated with a spin-density-wave (SDW) formation [19]. At higher temperature, the resistivity shows a Fermiliquid behavior varying as ρ(T ) = ρ 0 + AT 2 up to the coherence temperature T * ∼ 140 K, above which an incoherent bad-metal state is realized.…”
Section: Introductionmentioning
confidence: 99%
“…However, the internal magnetic field of the ordered state, ν µ (0 K), is found to be ∼3 MHz for Na [16,18] The muon locates probably ∼0.1 nm away from the oxygen ions, and there is no space for it in the CoO 6 octahedra in the [CoO 2 ] plane as in the case for the high-T c cuprates [25]. This discrepancy is difficult to explain only by differences in the µ + site experiencing the SDW field.…”
Section: B Magnitude Of Internal Magnetic Fieldmentioning
confidence: 99%
“…Furthermore, the µ + SR result suggested that the ordered phase below T m could be either a ferrimagnetic (FR) or a commensurate (C) spin density wave (SDW) state. [15] On the other hand, the related compound, pure and doped [Ca 2 CoO 3 ] RS 0.62 [CoO 2 ] (RS denotes the rocksalttype susbsystem), exhibited a transition to an incommensurate (IC) SDW state below ∼100 K. [16] Recent µ + SR experiment using both single crystals and c-aligned polycrystals suggested that long-range IC-SDW order forms below ∼ 30 K (≡ T SDW ), while a short-range order appears below 100 K (≡ T on c ). [17,18] Also, the IC-SDW was found to be induced by the ordering of the Co spins in the CoO 2 planes.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,3,4,5] Several researchers reconfirmed later the existence of long-range magnetic order in the layered cobaltites by not only µ + SR [6] but also neutron diffraction experiments. [7] These cobaltites share a common structural component as a conduction path, i.e., the CoO 2 planes, in which a two-dimensional-triangular lattice of Co ions is formed by a network of edge-sharing CoO 6 octahedra.…”
Section: Introductionmentioning
confidence: 93%